Implications of central bank backed digital currencies (crypto currencies) on monetary policy, financial stability and balance sheets : an exploratory scenario analysis - Francesevic, Marko; Schuster, Marco (München : GRIN Verlag, 2019)
Inspired by the recent publication of various Central Banks that study the issuance of their own versions of digital currencies, this paper aims at identifying the implications of such a central bank issued digital currency on monetary policy, financial stability and non-bank private sector, central bank and commercial bank balance sheet. It does so by conducting a scenario analysis, where each scenario specifies a distinct form of how a central bank issued digital currency could be introduced and how the resulting implications on the spheres of interest might change as a consequence. The results of this scenario analysis propose that in either implementation mode a CBDC generally provides a positive effect on both financial stability and monetary policy. The degree of the advantageous effect is, however, not only dependent on the implementation scenario, but also on the behaviour of the central banks, the commercial banks and the general public. In terms of balance sheets, this paper identified major changes. The results and implications that have been derived are based on literature, an expert interview and previous research conducted by other central banks and notable scholars. Based on the implications stemming from the four investigated scenarios, this paper evaluates these implications from a perspective of the New Currency School and Banking School. All in all, since this paper sees a central bank backed digital currency as a potential catalyst for a substantial change of the current monetary system, it provides scenarios and theories that challenge the status quo.
A Master's Thesis of the Magisterarbeit Copenhagen Business School, 2018
Includes bibliographical references
oif 18/06/2021
Loans
Keywords: Cryptocurrencies; Digital currencies---Central Banks